2018
DOI: 10.1186/s12906-018-2140-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling and in vitro screening for anticholinesterase, antioxidant, antiglucosidase and neuroprotective effect of three traditional medicinal plants for Alzheimer’s Disease and Diabetes Mellitus dual therapy

Abstract: BackgroundExtensive epidemiological and clinical studies revealed that Alzheimer’s Disease (AD) and Type 2 Diabetes Mellitus (T2D) are most likely to appear simultaneously in aged people as T2D is a major risk factor for AD. Therefore, development of potential multifunctional agents for dual therapy of AD and T2D has received much attention. Buchanania axillaris, Hemidesmus indicus and Rhus mysorensis have been used extensively in popular medicine. The present study was aimed at phytochemical profiling and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…Hence, we can convey that methanol extract of H. indicus has considerable AChE inhibitory potential against Aβ (1-42) infused AD model and dose-dependently inhibited the intracellular AChE activity in the rat brain. Our results are inconsistent with the previous indings by researchers, which reported that different extracts of H. indicus have successfully inhibited AChE activity (Kundu and Mitra, 2013;Penumala et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
“…Hence, we can convey that methanol extract of H. indicus has considerable AChE inhibitory potential against Aβ (1-42) infused AD model and dose-dependently inhibited the intracellular AChE activity in the rat brain. Our results are inconsistent with the previous indings by researchers, which reported that different extracts of H. indicus have successfully inhibited AChE activity (Kundu and Mitra, 2013;Penumala et al, 2018).…”
Section: Resultscontrasting
confidence: 99%
“…In this assay, the test samples were performed spectrophotometrically for AChE and BuChE inhibition potential using AChEI and BuChEI as substrates following the method of Ellman et al with minor changes [16, 43]. The test sample stock solution was prepared in the concentration of 1.0 mg/mL and then diluted into 500, 250, 125, 62.5, 31.05, and 15.625 μ g/mL solutions in order to select the appropriate concentration range of IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Acetylcholine (ACh), closely associated with AD, was a neurotransmitter responsible for the cognitive function, learning, and memory. According to the “cholinergic hypothesis,” acetylcholinesterase (AChE), a key enzyme in biological nerve conduction, was mainly associated with the degradation of ACh [15, 16]. In addition, there were some studies on neurotransmitter dysfunction such as dopamine and 5-hydroxytryptamine, but not much as ACh in AD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of AD syndrome in the elderly stage include the social and occupational activities hindrance. It is known to cause dementia in about 80% of individuals, according to recent findings [ 2 – 5 ] . Diagnosis of AD comprises of two well-known abnormalities, that is memory loss and defects in normal function of speaking, attention, thought, sense of judgement or problem solving [ 6 ].…”
Section: Introductionmentioning
confidence: 99%